Lanskap Linguistik di Kawasan Wisata Sanur: Kajian Kontestasi Bahasa - Hartanti Woro Susianti; Christina Purwanti; I Made Sutama (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study examines the linguistic landscape in the Sanur tourist area, Bali, as a representation of social, cultural, and ideological dynamics in the context of tourism globalization. Sanur as a multilingual public space displays the diversity of language use on signs, banners, billboards, and shop facades that reflect the interaction between local and global languages. Using a qualitative descriptive approach, an analysis was conducted on visual documentation and the social context of text use in public spaces, and linked to regional language preservation policies, especially Bali Provincial Regulation Number 1 of 2018. The results of the study show the dominance of English as a symbol of global economic power and the main communication tool in the tourism sector, while Balinese is used more symbolically as a local cultural identity. Ideologically, the Sanur linguistic landscape shows the negotiation between cultural preservation and the commodification of local identity amidst global market pressures. This study emphasizes that public space is not just an arena for communication, but also a field of representation of power, resistance, and cultural capital.